Cover Image, Volume 529, Issue 4. Issue 4 (1st January 2021) - Hutson, Kendall A.; Pulver, Stephen H.; Ariel, Pablo; Naso, Caroline; Fitzpatrick, Douglas C.
Abstract : The cover image is based on the Research Article Light sheet microscopy of the gerbil cochlea by Kendall A. Hutson et al., https://doi.org/10.1002/cne.24977 .